Modern tendencies in the higher education of young women - Barber, Ethel (My University, 1907)
Introduction: The higher education of women in America is now in progress on a vast scale, and in a variety of ways. Every phase of this great experiment, we choose to call it, may be studied almost simultaneously. Women are taking advantage of all the various kinds of education offered them and, considering the short period of time that this education has been offered them, about thirty years, we see how eager they are for education. Butler says in his essay on Education for Women, "The higher education of women naturally divides itself into, college education designed primarily to train the mental faculties by means of a liberal education and, secondarily to equip the student for self support and professional or special education, directed primarily toward one of the money making occupations." What is meant by higher education? It is the long course of education which the most thoroughly trained young American can get, a course which covers about twenty years between the sixth and the twenty sixth or twenty seventh years. The higher education is that which he receives after he is eighteen or nineteen years of age, that which he receives in the college or university after common school life is ended, and usually after his home life with his parents is over. It ordinarily covers three or four years of instruction in what are called the liberal arts or sciences, and after that period, a professional training which requires both special learning and special skill. The higher education thus covers a period of six to seven years. "The history of the education of a people, or an age is the history of its civilization, of its intellectual, moral and religious life, its material progress being incidental and subordinate." Higher education is not alone preparation of great people for great things. Higher education may prepare little men for greater things than they would have otherwise found possible, and so it is with women.
Citation: Barber, Ethel. Modern tendencies in the higher education of young women. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Higher Education; Women in Higher Education; History of Women in Higher Education; Theses